Aluminizing as a method of improvement of Mar-M247 alloy lifetime - Zagula-Yavorska, Maryana (Journal of Mining and Metallurgy, Section B: Metallurgy, 2024)
Environmentally friendly HTHA and HTLA CVD aluminizing processes were realized on the Mar-M247 heat resistant superalloy substrate, that is widely used in the hot part of aircraft engines. Additionally, commercially aluminide coatings deposited in the above-the-pack aluminiznig process were analyzed. Aluminizing of the Mar-M247 superalloy by the HTHA,  HTLA and above-the-pack processes led to formation of two layers of the coatings. The outer layer of coatings formed by the above-the-pack process consisted of the β-NiAl phase with substrate precipitates, while the outer layer of coatings formed by the HTHA and HTLA processes consisted of the pure β-NiAl phase. Aluminizing successfully improved lifetime of Mar-M247 superalloy. Despite the fact that coatings formed by the above-the-pack process is thicker and more aluminium concentration was found than those formed by the HTLA aluminizing and process, the lifetime of coated superalloy was lower. Moreover the oxidation resistance of the coated superalloy in the HTLA aluminizing process was better than those coated by the HTHA aluminizing process. The removal of impurities in the HTLA aluminizing process ensured a “pure” outer layer of coatings. Clean aluminide coatings may create a purer alumina oxide and may prolong its lifetime.
Keywords: HTLA process, HTHA process, above-the-pack process, lifetime